Development and evaluation of bioadhesive buccal films based on sodium alginate for allergy therapy - Krisztián Pamlényi; Katalin Kristó; Tamás Sovány; Géza Regdon jr. (Heliyon, 2022)
Buccal drug administration is a less explored area, therefore researchers and companies focus on its research because of its innovative potential and opportunities. Buccal polymer films (patches) are considered to be an innovative form and have a great number of advantageous properties. Firstly, patients who suffer from swallowing problems and children can also apply them. The active pharmaceutical ingredient enters the systemic circulation directly without degradation and transformation. The aim of this study was to formulate buccal films with sodium alginate (SA) because it is a rarely used, innovative polymer for the formulation of buccal films. The mechanical, chemical properties and dosage forms of the prepared films were investigated with different methods. To formulate the films, cetirizine dihydrochloride (CTZ) was used as model drug, and glycerol (GLY) was added to make the films more elastic. The samples were prepared and stored at room temperature. As a result, it can be seen that the mechanical properties of all film compositions show good results, especially breaking hardness. The films with high SA concentration containing CTZ had appropriate mucoadhesion forces, so these samples are suitable for application on the buccal mucosa. The results of dissolution confirmed this finding. Finally, it can be said we formulated fast dissolving films and it can be concluded that the films prepared with 3% SA concentration containing 1% and 3% GLY can be recommended for buccal application.